2012
DOI: 10.1029/2011gc003929
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical model reconciles contradictory geophysical observations at the Dead Sea Basin

Abstract: [1] The Dead Sea Transform (DST) comprises a boundary between the African and Arabian plates. During the last 15-20 m.y. more than 100 km of left lateral transform displacement has been accumulated on the DST and about 10 km thick Dead Sea Basin (DSB) was formed in the central part of the DST. Widespread igneous activity since some 20 Ma ago and especially in the last 5 m.y., thin (60-80 km) lithosphere constrained by seismic data and absence of seismicity below the Moho, seem to be quite natural for this tect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 91 publications
(119 reference statements)
1
11
0
Order By: Relevance
“…Thermomechanic simulations also suggest that the DSB can be considered as a classical pull-apart basin, assuming that the lithosphere was thermally eroded at about 20 Myr. and an uppermost mantle with relatively weak rheology, which would be consistent with lab data for wet olivine or pyroxenite (Petrunin et al 2012). In addition, the low friction coefficients required to model the architecture of the DSB thermomechanically and the high subsidence rate of the basin sediments suggest the presence of hydrous minerals within the FZC.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 83%
See 3 more Smart Citations
“…Thermomechanic simulations also suggest that the DSB can be considered as a classical pull-apart basin, assuming that the lithosphere was thermally eroded at about 20 Myr. and an uppermost mantle with relatively weak rheology, which would be consistent with lab data for wet olivine or pyroxenite (Petrunin et al 2012). In addition, the low friction coefficients required to model the architecture of the DSB thermomechanically and the high subsidence rate of the basin sediments suggest the presence of hydrous minerals within the FZC.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 83%
“…Alteration of granitic rocks which include Feldspar to varieties of hydrous minerals including Muscovite have been observed at deeper levels in many fault zones (Etheridge et al 1983;Bruhn et al 1990). Based on thermomechanic modelling, Petrunin et al (2012) suggested that the state of the DSB as a classical pull-apart basin can be explained by thermal erosion of the lithosphere before approximately 20 Myr. As a consequence, we would expect relatively weak rheology of the uppermost mantle which would be consistent with the occurrence of wet olivine or pyroxenite (Petrunin et al 2012).…”
Section: Discussion O F T H E 2 -D E L E C T R I C a L C O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Most scholars associate the origin of deep linear depressions along the DST, such as the Gulf of Aqaba and the Dead Sea, with the pullapart mechanism (Mann et al, 1983;Makovsky et al, 2008;Petrunin and Sobolev, 2008;Hartman et al, 2014). In this context, lateral displacements along a non-straight fault line should lead to the origin of compression and extension zones at the vicinity of the fault, and many studies have used both numerical modeling (Petrunin and Sobolev, 2008;Petrunin et al, 2012) and geological evidence (Ehrhardt et al, 2005) to demonstrate the possibility of such a scenario. Alternatively, the origin of the present depressions along the DST can be explained by the relative transform-normal extension (Ben-Avraham and Zoback, 1992;Smit et al, 2010) due to relocation of the pole of rotation for the DST at about 5 Ma (Garfunkel, 1981).…”
Section: Geological Settingmentioning
confidence: 99%